PBL Blueprinting Toolbox - Anne Rudnicki; Era Buck; Oma Morey (Association of American Medical Colleges, 2015)
Abstract Introduction This toolbox was developed to help faculty and staff in medical education write and design problem-based learning (PBL) cases from scratch. From learning objectives to case narrative to facilitator's guide to formative and summative evaluation, this toolkit provides tools and templates to help PBL case developers craft educationally sound and rich cases. Components of the toolbox may also be useful when used independently for revising or enriching cases. Methods There are seven tools included in the toolbox. They are the Case Alignment Tool, the Clinical Reasoning Tool, the Storyboard Tool, the Multiple-Choice Item Writing Tool, the Student Case Slides Tool, the Facilitator Notes Tool, and the Case Evaluation Tool. The tools were implemented in the Great Syndromes and Cardiovascular and Pulmonary courses. We observed the groups and solicited feedback from course directors and facilitators as part of the evaluation process. Based on the feedback from the implementation, we made adjustments to the templates and presented the PBL Toolbox to the Operations Committee of the School of Medicine. Based on feedback from that group, additional minor revisions were made prior to presentation to the Curriculum Committee. The Curriculum Committee endorsed use of this template and instituted a new policy requiring that all new cases developed for use in our integrated curriculum use this resource. As a result, all courses went on to use and implement the tools in their PBL curricula. Results The toolbox has been used to revise 20 existing cases, including facilitator notes and student slides, in our PBL curriculum and develop five new cases. Faculty have reported in Curriculum Committee meetings that they find discussions in PBL sessions to have greater depth in cases that were revised using this resource. In addition, 70% of the facilitators in a course using the Facilitator Notes Tool reported that "the facilitator notes enhanced my effectiveness as a facilitator." Finally, we have seen a 10% increase in the duration of PBL sessions for cases developed utilizing the toolbox. Discussion Well-designed PBL cases activate prior knowledge and encourage elaboration and integration of new knowledge. The resources provided in this toolbox help PBL case developers to create these educationally sound and rich cases.